2019
DOI: 10.1155/2019/4596127
|View full text |Cite
|
Sign up to set email alerts
|

Leukotriene Involvement in the Insulin Receptor Pathway and Macrophage Profiles in Muscles from Type 1 Diabetic Mice

Abstract: Type 1 diabetes (T1D) is a metabolic disease associated with systemic low-grade inflammation and macrophage reprogramming. There is evidence that this inflammation depends on the increased systemic levels of leukotriene (LT) B4 found in T1D mice, which shifts macrophages towards the proinflammatory (M1) phenotype. Although T1D can be corrected by insulin administration, over time T1D patients can develop insulin resistance that hinders glycemic control. Here, we sought to investigate the role of leukotrienes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 25 publications
0
8
0
14
Order By: Relevance
“…All revealed violations occurred on the background of increased level of IL-6 and decreased IL-13 level in the blood serum, which implied the chronic inflammatory process in patients with diabetes. It is known that chronic increasing of IL-6 amount causes damages to the skeletal muscles as a result of intercellular signals transferring and leads to loss of myofibrillar protein and muscle atrophy [8,31]. Moreover, IL-6 reduces the transferring of insulin signals to skeletal muscles, which causes the reduced amount of glucose transported inside [15].…”
Section: Discussing the Received Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All revealed violations occurred on the background of increased level of IL-6 and decreased IL-13 level in the blood serum, which implied the chronic inflammatory process in patients with diabetes. It is known that chronic increasing of IL-6 amount causes damages to the skeletal muscles as a result of intercellular signals transferring and leads to loss of myofibrillar protein and muscle atrophy [8,31]. Moreover, IL-6 reduces the transferring of insulin signals to skeletal muscles, which causes the reduced amount of glucose transported inside [15].…”
Section: Discussing the Received Resultsmentioning
confidence: 99%
“…Guimarães, et al (2019) experimental investigation. He revealed that the higher expression of IL-6 had correlations with lower expression of receptors to insulin in muscles of mice with diabetes WT [8].…”
Section: Discussing the Received Resultsmentioning
confidence: 99%
“…Diabetes mellitus is a chronic disorder characterized by persistent levels of hyperglycemia caused by an insufficient production of insulin by the β cells of the pancreas due to a destruction of these cells in type 1 diabetes (T1D) or by ineffective insulin action in type 2 diabetes (T2D) [ 1 – 3 ]. Rodents have been extensively used as diabetes experimental models [ 4 ]—chemically induced diabetes is mainly useful for studying T1D.…”
Section: Introductionmentioning
confidence: 99%
“…Diferentes materiais foram introduzidos nas gaiolas para enriquecer o ambiente dos animais (algodão, iglu, tubos de papelão, etc).Foram incluídos no estudo animais adultos jovens e machos que apresentaram perda de peso, acompanhada de glicemia superior a 300 mg/dL (16,6 mM), após administração de ALX e STZ, conforme delineamento descrito a seguir. Não foram incluídos os animais com glicemia inferior a 300 mg/dL após o uso dos agentes diabetogênicos(AYALA et al, 2019;GUIMARÃES et al, 2019). Para a indução de DM1 com STZ, os animais foram deixados em jejum de 5 horas, antes de receberem injeção intraperitoneal (i.p) de STZ (65 mg/kg; 300µL) dissolvida em tampão citrato de sódio a 0,05 M gelado (pH 4,0-4,5) por 5 dias consecutivos (Figura 6)(GUIMARÃES et al, 2019).…”
unclassified
“…Não foram incluídos os animais com glicemia inferior a 300 mg/dL após o uso dos agentes diabetogênicos(AYALA et al, 2019;GUIMARÃES et al, 2019). Para a indução de DM1 com STZ, os animais foram deixados em jejum de 5 horas, antes de receberem injeção intraperitoneal (i.p) de STZ (65 mg/kg; 300µL) dissolvida em tampão citrato de sódio a 0,05 M gelado (pH 4,0-4,5) por 5 dias consecutivos (Figura 6)(GUIMARÃES et al, 2019).…”
unclassified